2022
DOI: 10.3390/molecules27228005
|View full text |Cite
|
Sign up to set email alerts
|

Triptonoterpene, a Natural Product from Celastrus orbiculatus Thunb, Has Biological Activity against the Metastasis of Gastric Cancer Cells

Abstract: Cancer is one of the greatest threats to human health. Gastric cancer (GC) is the fifth most common malignant tumor in the world. Invasion and metastasis are the major difficulties in the treatment of GC. Herbal medicines and their extracts have a lengthy history of being used to treat tumors in China. The anti-tumoral effects of the natural products derived from herbs have received a great deal of attention. Our previous studies have shown that the traditional Chinese herb Celastrus orbiculatus Thunb extract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The patent number is 200710025343.3. At the same time, it was found that the COE can inhibit the activity of various digestive tract tumors ( Jin et al, 2018 ; Qian et al, 2018 ; Lv et al, 2022 ; Wang et al, 2022 ). COE can induce apoptosis, block the cell cycle, and inhibit the proliferation of gastric cancer cells ( Qian et al, 2019 ; Tao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 98%
“…The patent number is 200710025343.3. At the same time, it was found that the COE can inhibit the activity of various digestive tract tumors ( Jin et al, 2018 ; Qian et al, 2018 ; Lv et al, 2022 ; Wang et al, 2022 ). COE can induce apoptosis, block the cell cycle, and inhibit the proliferation of gastric cancer cells ( Qian et al, 2019 ; Tao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 98%